Influence of Rainfall and Rain Day on Rubber Production 7, 10, 13 Years Aged in Sei Baleh Estate PT. Bakrie Sumatera Plantations, Tbk - Dewi Merantika Sinaga; Irsal Irsal; Lisa Mawarni (Universitas Sumatera Utara, 2017)
One of determining factors of water supply for rubber plants are rain fall and rain day. Water supply for rubber in field is obtained from rainfall. The amount of water that doesn’t consistent give negative impact to the productivity of rubber. This research was to determine the effect of rainfall and rain day as well as the correlation of both on rubber production in plants 7, 10 and 13 years aged. This research is done in Sei Baleh Estate PT. Bakrie Sumatera Plantations, Tbk. from January to March 2016. Primary data for the purposes of data analysis includes latex production in 2012, 2013, and 2014; rainfall data and rain day monthly in 2011, 2012, and 2013. Analysis method used are double linier regression and correlation analysis. Model tested by classic asumption consists of normality test, heteroskedasticity test, multicollinearity, and autocorellations test by using statistic software SPSS.v.17 for windows. The regression analysis shows that rainfall and rain day variables don’t have significant influence to increased latex production of rubber plants 7, 10 and 13 years aged. Rainfall and rain day affect latex production 19,1%; 9,3%; 28,6% of rubber plants 7, 10 and 13 years aged. The correlation result in plants aged 7 and 10 years showed variable rainfall and rain day have a strong relationship (0,921 and 0,901) against the latex production, meanwhile in plants aged 13 years have a sufficient relationship (0,776).